Stimulating non-energy exports in Trinidad and Tobago: Evidence from a small petroleum-exporting economy experiencing the Dutch disease - Roger Hosein; Leera Boodram; George Saridakis (Journal of Risk and Financial Management, 2022)
The motivation for this study hinges around the fact that Trinidad and Tobago (T&T) is suffering from the Dutch disease which inadvertently hinders the growth of non-energy exports. This paper examines measures that can be adopted for a small petroleum-exporting economy to dampen the effect of Dutch disease by promoting non-energy trade. This paper is novel and contributes to the literature in using panel data for the T&T case, as it investigates the effect of a devaluation of the TT dollar in order to stimulate non-energy exports (a combination of agriculture and manufacturing trade). Note that previous studies would have examined the Marshall-Lerner condition on the aggregate trade balance which is heavily influenced by energy revenues. The panel autoregressive distributed lag (ARDL) method is used for ten of T&T's main trading partners for the period 1991 to 2019 to establish findings. The results show that the Marshall-Lerner condition does not hold for aggregate trade in the long run, as expected. However, when non-energy trade is isolated, it is found that a devaluation of the TT dollar does have a positive impact on non-energy trade and the Marshall-Lerner condition holds. Other measures are also recommended to stimulate non-energy exports in the long run.
Keywords: 330; Trinidad and Tobago; Marshall-Lerner condition; non-energy trade